The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/s1995-7645(14)60157-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alprostadil combined with Diammonium glycyrrhizinate on renal interstitial fibrosis in SD rats

Abstract: Alprostadil combined with diammonium glycyrrhizinate can significantly lower the expression of TGF - β1 and CTGF in serum and tissues of SD rat with renal interstitial fibrosis, thus inhibit rat renal interstitial fibrosis process. It has synergy protective effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…However, the histologic features of these two rats were not occurred obvious abnormality after recovery period, which may be because the injury degree was not serious enough to cause pathological changes. Secondly, as we known, the fluctuation range of SD rats' serum CREA is widely, and various among different study reports (Iga et al, 2010 ; Zhao et al, 2011 ; Cai et al, 2014 ). According to these results, although the CREA value (42.2 ± 6.1 μM) was increased in Arctigenin 12 mg/kg group, this difference within normal fluctuation range.…”
Section: Discussionmentioning
confidence: 95%
“…However, the histologic features of these two rats were not occurred obvious abnormality after recovery period, which may be because the injury degree was not serious enough to cause pathological changes. Secondly, as we known, the fluctuation range of SD rats' serum CREA is widely, and various among different study reports (Iga et al, 2010 ; Zhao et al, 2011 ; Cai et al, 2014 ). According to these results, although the CREA value (42.2 ± 6.1 μM) was increased in Arctigenin 12 mg/kg group, this difference within normal fluctuation range.…”
Section: Discussionmentioning
confidence: 95%
“…Studies have shown that PGE1 can dilate renal vessels, increase renal blood flow, and increase CrCl, which has a protective effect on renal function, and then prevent the occurrence and development of CIN. 21 Its main renal protective effect is to dilate renal vessels, inhibit platelet aggregation, and achieve renal vascular relaxation balance without systemic hypotension. 22,23 Prostaglandin E1 exerts an effect through nonspecific, dose-dependent, reversible indirect inhibition of lymphokine-mediated actions.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] The main component of alprostadil is prostaglandin E1 (PGE1), which is blood vessel-expanding agent that can dilate kidney and renal blood vessels, increases renal blood flow, inhibits platelet aggregation, prevents renal microvascular thrombosis, reduces renal blood viscosity, inhibits inflammatory mediators, maintains renal perfusion, and reduces urinary protein synthesis. 12,13 Some animal studies have shown that PGE1 has a protective effect on renal by reducing the number of NF-kBþ, caspase-3þ inflammatory cells, and NF-kB DNAbinding activity; increasing proliferating cell nuclear antigenþ epithelial cells; inhibiting the expression of intracellular adhesion molecule 1; ameliorating the renal microvascular injury; relieving hypoxia; and protecting renal function. [17][18][19] Therefore, alprostadil may be a new drug to prevent the occurrence of CIN.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] Alprostadil, a potent renal dilatator, has some protective effects on renal function, such as expanding renal blood vessels, increasing renal blood flow, inhibiting platelet aggregation, protecting vascular endothelial cells, reducing vasoconstrictor effect, stabilizing lysosomal membranes, decreasing blood viscosity and erythrocyte aggregation, and improving erythrocyte deformability, which may be beneficial in reducing CIN. 12,13 Some studies showed that alprostadil plays a prophylactic role in the development of CIN, 14,15 but most of the studies were single center and of small sample size, so the exact preventive role of alprostadil in CIN remains unclear. Therefore, the purpose of this study is to investigate whether alprostadil could reduce the incidence of CIN in patients with renal insufficiency undergoing PCI.…”
Section: Introductionmentioning
confidence: 99%